ST-Elevation Myocardial Infarction Among Septic Shock and Coronary Interventions: A National Emergency Database Study. (August 2022) - Mir, Tanveer; Uddin, Mohammed; Qureshi, Waqas T.; Abohashem, Shady; Alqalyoobi, Shehabaldin; Sheikh, Mujeeb; Soubani, Ayman; Saydain, Ghulam; Albertson, Timothy E.
Objective: To study coronary interventions and mortality among patients with ST-elevated myocardial infarction (STEMI) who were admitted with septic shock. Methods: Data from the national emergency department sample (NEDS) that constitutes 20% sample of hospital-owned emergency departments in the United States was analyzed for the septic shock related visits from 2016 to 2018. Septic shock was defined by the ICD codes. Results: Out of 1 375 507 adult septic shock patients, 521 300 had a primary diagnosis of septic shock (mean age 67.41±15.67 years, 51.1% females) in the national emergency database for the years 2016 to 2018. Of these patients, 2768 (0.53%) had STEMI recorded during the hospitalization. Mortality rates for STEMI patients were higher than patients without STEMI (52.3% vs 23.5%). Mortality rates improved with PCI among STEMI patients (43.8% vs 56.2%). Coronary angiography was performed among 16% of patients of which percutaneous coronary intervention (PCI) rates were 7.7% among patients with STEMI septic shock. PCI numerically improved mortality, however, had no significant difference than patients without PCI on multivariate logistic regression and univariate logistic regression post coarsened exact matching of baseline characteristics among STEMI patients. Among the predictors, STEMI was a significant predictor of mortality in septic shock patients (OR 2.87, 95% CI 2.37-3.49; P <.001). Age, peripheral vascular disease, were predominant predictors of mortality in STEMI with septic shock subgroup ( P <.001). Pneumonia was the predominant underlying infection among STEMI (36.4%) and without STEMI group (29.5%). Conclusion: STEMI complicating septic shock worsens mortality. PCI and coronary angiography numerically improved mortality, however, had no significant difference from patients without PCI. More research will be needed to improve mortality in such a critically ill subgroup of patients.